PO 8208 Cytokine profiles in sudanese children presented with severe malaria, uncomplicated malaria compared to healthy community controls according to WHO criteria. (24th April 2019) - Hamdan, Hamdan; El-Misbah, Muna; El-Awad, Tasneem
Abstract : Background: Immune system response to Plasmodium falciparum ( P. falciparum ) malaria infection outlines the disease course and outcome. This is attributed to variable production of cytokines that either promote (pro-inflammatory) or curtail (anti-inflammatory) the inflammatory process. Elucidating underlying immunological disease interactions may direct development of effective treatment and provide better understanding of the disease process. Methods: A case control study was conducted in Mohamed Elamin Paediatrics Hospital (March- August 2016) in Omdurman in central Sudan, an area that is characterised by unstable malaria transmission. The study aims to investigate the role/interaction of cytokine profiles of gamma interferon (IFN-γ) and Interleukin-10 (IL-10) in children infected with P. falciparum malaria. Enzyme-linked immunosorbent assay was used to measure the concentrations of cytokines, IFN- γ and IL-10, in serum from Sudanese children. Thirty–five children with complicated P. falciparum malaria were enrolled to the study; well-matched 35 uncomplicated P. falciparum malaria and another 35 healthy children were controls. Informed written consent was obtained from the parents or guardian. Complete blood count, blood urea and random blood glucose were measured by using standard laboratory procedures. Results: The concentrations of IFN-γ and IL-10 levels were significantly higher in children with severe malaria compared to uncomplicated malaria and healthy control. There was a strong positive correlation observed between IL-10 and IFN-γ (r=0.688 p=<0.001, as well as a strong positive correlation detected between IFN-γ and urea levels (r=0.73; p=0.010). There was moderate correlation between IL-10 and urea (r=0.386; p=<0.001). While negative moderate correlation was observed between IL-10 and haemoglobin levels (r=−0.316; p=0.003), no correlation was detected between IFN-γ and haemoglobin levels. All patients were discharged home in good condition. Conclusion: These results indicate both IFN- γ and IL-10 are involved in shaping the course and outcome of the severe malaria in children.